Takhrij and Syarah Hadith of Chemistry: The Use of Soil as an Unclean Medium Mughalladzah in a Chemical Perspective - Ashab Abdul Hakim; Erni Isnaeniah (International Journal on Orange Technologies, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad. about the use of land as a medium for cleaning unclean mughalladzah. This research method is qualitative through the approach of takhrij and sharah hadith with chemical analysis. The results and discussion of this research is that soil has played an important role in cleaning or purifying the unclean mughalladzah from the time of the Prophet and with its provenance in the field of chemistry, it further confirms and justifies the role of soil as a medium for cleaning unclean mughalladzah. The conclusion of this research is takhrij and syarah hadith of the Prophet. regarding the use of soil as a medium for cleaning unclean mughalladzah with chemical analysis has been proven to be able to clean bacteria from dog saliva which is the cause of unclean mughalladzah.